Electrochemotherapy in locally advanced pancreatic cancer: Preliminary results. (June 2015) - Granata, V.; Fusco, R.; Piccirillo, M.; Palaia, R.; Petrillo, A.; Lastoria, S.; Izzo, F.
Abstract: Objective: Report the preliminary results on electrochemotherapy (ECT) in the treatment of locally advanced pancreatic cancer of a phase I/II study and described the new functional imaging tools to assess ECT response in Magnetic Resonance (MR) imaging compared to morphological Computer Tomography (CT), ultrasound (US) without and with contrast enhancement (CEUS) and MR Imaging. Materials and methods: Thirteen patients were enrolled in an ongoing clinical phase I/II study approved by Ethical Committee of National Cancer Institute G. Pascale Foundation – IRCCS of Naples. ECT with bleomycin was performed during open surgery. All patients underwent US and CT scan, before and after ECT treatment; 7 patients were evaluated using morphological and functional (dynamic contrast enhancement-DCE and diffusion weighted- DW) parameters in MR; 5 patients underwent CEUS. RECIST criteria were used to evaluate ECT response on US, CT and MR images. Functional parameters were also used to evaluate ECT response on MR images. Results: No acute (intraoperative) and/or postoperative serious adverse events related to electrochemotherapy were observed; no clinically significant electrocardiographic, hemodynamic, or serum biologic changes were noted. No clinically relevant elevation of amylase or lipase levels was observed and no bleeding or damage to surrounding viscera occurred. In three patients had seen splenic infarction without thrombosis of the splenic vessels. Conclusion: Electrochemotherapy is feasible and safe treatment modality in patients with locally advanced pancreatic adenocarcinoma. Dynamic and diffusion MR imaging in comparison to MR morphological sequence alone and to UC and CT imaging is more suitable to assess ECT treatment response. CEUS is not indicated in follow up after ECT. Highlights: Electrochemoterapy can treat patients with locally advanced pancreatic adenocarcinoma. We have recordered no side effects or major complications with good functional result. No damage to surrounding viscera that required medical or surgical treatment.